Efektivitas Akuntansi Forensik dan Audit Investigasi dalam Pencegahan dan Deteksi Fraud - Warda Toatubun; Ainun Arizah (AKUNTANSI 45, 2025)
This study aims to clarify and deepen understanding of the effectiveness of forensic accounting and audit investigations in fraud prevention and detection. Using a descriptive approach and literature review, this study examines various scientific sources related to the concepts, techniques, and effectiveness of both fields. The study's findings demonstrate that forensic accounting plays a strategic role in uncovering fraud cases because it can generate strong legal evidence through the application of in-depth forensic analysis techniques, such as document examination, digital data analysis, and transaction reconstruction. Investigative audits, on the other hand, identify weaknesses in internal controls so organizations can implement policy improvements to minimize the potential for future fraud. This study also confirms that the synergy between investigative and forensic analysis methods can strengthen oversight systems and increase transparency and accountability. This combination not only helps detect fraud more effectively but also supports the implementation of better governance within an organization.